Mapping progress in intravascular catheter quality surveillance: An Australian case study of electronic medical record data linkage - Schults, Jessica A.; Ball, Daner L.; Sullivan, Clair; Rossow, Nick; Ray-Barruel, Gillian; Walker, Rachel M.; Stantic, Bela; Rickard, Claire M. (Frontiers in Medicine, 2022)
Background and significance: Intravascular catheters are the most invasive medical device in healthcare. Localized priority-setting related to intravascular catheter quality surveillance is a key objective of recent healthcare reform in Australia. We sought to determine the plausibility of using electronic health record (EHR) data for catheter surveillance by mapping currently available data across State-wide platforms. This work has identified barriers and facilitators to a State-wide EHR surveillance initiative. Materials and Methods: Data variables were generated and mapped from routinely used EHR sources across Queensland, Australia through a systematic search of grey literature and expert consultation with clinical information specialists. EHR systems were eligible for inclusion if they collected data related to intravascular catheter insertion, care, or outcomes of hospitalized patients. Generated variables were mapped against international recommendations for intravascular catheter surveillance, with data linkage and data export capacity narratively summarised. Results: We identified five EHR systems; iEMR, MetaVision ICU®, Multiprac, RiskMan, and the Nephrology Registry. Systems were used across jurisdictions and hospital wards. Data linkage was not evident across systems. Extraction processes for catheter data were not standardised, lacking clear, reliable extraction techniques. In combination, EHR systems collected 43/50 international variables recommended for catheter surveillance, however individual systems collected a median of 24/50 (IQR 22, 30) variables. We did not identify integrated clinical analytic systems (incorporating machine learning) to support clinical decision making or for risk stratification (e.g., catheter-related infection). Conclusion: Current data linkage across EHR systems limits the development of an intravascular catheter quality surveillance system to provide timely data related to catheter complications and harm. To facilitate reliable and timely surveillance of catheter outcomes using clinical informatics, substantial work is needed to overcome existing barriers and transform health surveillance.